Team and Project Based Learning for a Sophomore Course on Digital System Design - Waychal, Pradeep (Journal of Engineering Education Transformations, 2016)
The paper describes our experience of using team-and project-based learning (TBL PBL) instructional strategy, which, despite strong evidence of efficacy, is underused - especially - in the early years of engineering education. We describe our framework FAME (form, allocate, monitor and evaluate) for operationalizing the strategy and illustrate it's usage for a sophomore course in digital system design. We found that the strategy resulted in students understanding basic concepts well and utilizing them in developing real life applications as well as developing teamwork, self-learning, and time management skills. We believe that the framework and our experience can be helpful to other faculty members to implement the TBL PBL strategy in their courses.